The implementation strategy of Ecosystem Approach to Aquaculture (EAA) shrimp commodities in Pinrang District, South Sulawesi - eddy supriyono; Wisriati Lasima; Muhammad Zairin Junior; Sugeng Budiharsono; Nirmala, Kukuh; Sukenda (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
This study aims to develop a strategy for the sustainability of shrimp aquaculture using an ecosystem approach or EAA in Pinrang Regency, South Sulawesi. A series of analyzes were carried out, namely the environmental carrying capacity analysis of aquaculture using pond environmental feasibility standards, analysis of critical factors for the sustainability of aquaculture using multidimensional scaling analysis, analysis of the sustainability status of aquaculture using pairwise comparison analysis and analysis of shrimp aquaculture management strategies based on EAA. using hierarchy process analysis. The results showed that the following strategies were needed: a) accelerating spatial planning and implementing programs in accordance with the directions for spatial use and control; b) institutional strengthening of capital cultivators in order to complement and improve facilities and infrastructure in accordance with the SOP; and c) increasing the level of education and providing a social and economic security system for members of the shrimp farming community